Who Distributes? Presidents, Congress, Governors, and the Politics of Distribution in Argentina and Brazil - Gonzalez, Lucas Isaac (2015)
What is the role of presidents in the politics of distribution in developing democracies? To what extent do other political actors, such as legislators and governors, influence federal distribution? This paper studies the main factors that affect distributive politics in Argentina and Brazil, two highly unequal presidential federations in Latin America. The focus is on funds with high redistributive impact and over which the central government has large discretion: those for public infrastructure. Using original data on federal infrastructure spending for the 24 provinces in Argentina and the 27 states in Brazil for the period 1999-2011, we show that the distribution of infrastructure funds is fundamentally determined by executive politics. Despite this, our empirical findings indicate there is large variation between the two cases in the relevance of the partisan links between presidents and governors and the influence of congress and its committees. Furthermore, we observe that elections are not relevant in explaining distribution in either of the two cases and that presidents are mostly motivated by political considerations and that programmatic factors, such as equity and efficiency criteria, play a secondary role, especially in Argentina. We discuss some possible reasons for these results and their implications for the broader comparative debate on distributive politics.